2015
DOI: 10.1039/c5nj01372k
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free amidation of aldehyde with amine under mild conditions

Abstract: A high efficient, catalyst-free and one-pot procedure for direct synthesis of amides from aldehydes and amines under mild conditions has been developed. Both aliphatic and aromatic aldehydes with primary or secondary amines are successfully converted to the corresponding amides, and 10 reactions can proceed in either aqueous or organic media.Amide units exist in a variety of natural products, biopharmaceuticals, polymers and materials [1] , which has been proved to have important applications in a wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In 2015, Wang's research team revealed a catalyst‐free one‐pot procedure for synthesising amide derivatives from amidation reaction of various aromatic and aliphatic aldehydes with 1° and 2° amines trichloroisocyanuric acid in either organic or aqueous media under mild conditions (Scheme 156). [297] …”
Section: C−h Bond Amidationmentioning
confidence: 99%
“…In 2015, Wang's research team revealed a catalyst‐free one‐pot procedure for synthesising amide derivatives from amidation reaction of various aromatic and aliphatic aldehydes with 1° and 2° amines trichloroisocyanuric acid in either organic or aqueous media under mild conditions (Scheme 156). [297] …”
Section: C−h Bond Amidationmentioning
confidence: 99%
“…Further development of this methodology was carried out by Wang and co‐workers to obtain amides from aldehydes and amines using TCCA as an oxidizing and chlorinating reagent (Scheme ) …”
Section: Tcca As Oxidizing Reagentmentioning
confidence: 99%
“…In 2015, Yang et al. described an efficient catalyst‐free procedure for the direct amidation of aldehydes with primary and secondary amines by using TCCA (Scheme ) . This reaction worked smoothly and efficiently in both aqueous solutions and organic solvents.…”
Section: Synthesis Of Amides From Aldehydesmentioning
confidence: 99%